Разработка модели экспериментального пародонтита = Development of the model of experimental periodontitis - Anna Vladimirovna Nikolaeva; Stanislaw Arkadievich Shnaider (Kazimierz Wielki University, 2015)
Nikolaeva A. V., Shnayder S. A. Разработка модели экспериментального пародонтита = Development of the model of experimental periodontitis. Journal of Education, Health and Sport. 2015;5(12):317-325. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35463 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A317-325 http://pbn.nauka.gov.pl/works/682215 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 16.12.2015.   УДК: 616.314.17-008.1-0.2-092.9(086.48):599.323.4 UDC: 616.314.17-008.1-0.2-092.9(086.48):599.323.4   РАЗРАБОТКА МОДЕЛИ ЭКСПЕРИМЕНТАЛЬНОГО ПАРОДОНТИТА   DEVELOPMENT OF THE MODEL OF EXPERIMENTAL PERIODONTITIS   А. В. Николаева, С. А. Шнайдер A. V. Nikolaeva, S. A. Shnayder   Государственное учреждение  «Институт стоматологии Национальной Академии Медицинских Наук Украины» SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine»   Реферат   В опытах на 14 белых крысах с помощью купренила (D-пеницилламина)  была воспроизведена экспериментальная модель пародонтита. Ксенобиотик купренил вызвал воспалительные явления в тканях пародонта и резорбцию его костных структур. Под влиянием купренила было выявлено разрушение коллагена и снижение уровня ГАГ десны. По данным морфологических исследований выявлено уменьшение объема соединительной ткани слизистой оболочки полости рта; уменьшение числа клеток, синтезирующих компоненты межклеточного вещества.   Ключевые слова: купренил, воспалительные явления, резорбция кости альвеолярного отростка, морфологические исследования, фибробласты, соединительная ткань, эпителиальный пласт, белые крысы.   A.V. Nikolaeva, S. A. Shnayder SE «The Institute of Stomatology National Academy of Medical Sciences of Ukraine» DEVELOPMENT OF THE MODEL OF EXPERIMENTAL PERIODONTITIS   Summary   Kuprenil - is a synthetic drug that is used for acute and chronic poisoning metals. Kuprenil has multilateral influence on the metabolism of collagen by blocking its synthesis. Under its influencetake place the binding of transverse collagen fibers. The study of mechanisms of damage MKM periodontal tissue in a play of his inflammatory diseases. The Aim of study was modeling of the experimental periodontitis and in connection with this study of the molecular mechanisms and cytomorphologic changes of metabolic disorders of the extracellular matrix and periodontal buccal mucosa of rats. Materials and methods. The experiments conducted on 14 white rats 1.5-2 months. age. Intact group consisted of 6 rats. The experimental model  of periodontitis was reproduced on the 8 rat  with introductionof the  kuprenil with drinking water in a dose of 20 mg / kg body weight of rats continuing for 55 days. Results and conclusions. Xenobiotic kuprenil caused the inflammation in the periodontal tissues and the resorption of its bone's structures. Under the influence of the kuprenil was revealed the destruction of collagen and GAG reduction of the gums. According to the morphological studies revealed a decrease in volume of the connective tissue of the oral mucosa; reducing the number of cells synthesizing components of the intercellular substance.             Key words: kuprenil, inflammatory effects, resorption of the alveolar bone, morphological studies, fibroblasts, connective tissue, epithelial layer, white rats.